The incidence of HPV infection of high carcinogenic risk in women of the Kemerovo region - Natalia V. Artymuk; Anastasia V. Breus; Dmitrii A. Artymuk (IP Berlin A.V., 2023)
Aim. Toassess the prevalence of various types of human papillomavirus (HPV) of high carcinogenic risk (HCR) and the rate of abnormal findings of cytological examination in HPV-positive and HPV-negative women of the Kemerovo region. Materials and methods. A continuous cross-sectional study was conducted. The study included 675 women aged 21 to 65 (mean age 40.510.6 years) residing in the Kemerovo region. Patients were sampled from the cervical canal for semi-quantitative HPV-typing and cytological examination with Papanicolaou staining (PAP-test) using a liquid-based cytology method. For HPV-positive patients, an HPV typing with the quantification of 14 HCR HPV types was performed by polymerase chain reaction with real-time detection. Statistical data processing was performed using the StatSoft Statistica 6.1 software bundle. Results. The mean rate of HCR HPV detection in women of the Kemerovo region in the age group of 2165 years is 17.8% and decreases with age. HPV type 16 prevailed and was detected in 31.6% of women. In 19.2% of women, the HPV subtype 31 was diagnosed; in 18.3%, the subtype 35; in 16.7%, the subtype 33. The HPV subtypes 39, 56, and 66 were the rarest. One subtype of HCR HPV was detected in 26.7% of women, two subtypes in 6.7%, and three or more subtypes in 66.6% of women. According to the cytological examination, CIN 1, 2, and 3 rates were 3.3, 0.8, and 0.7%, respectively. HSIL (CIN 23) was detected in 1.5% of cases, LSIL (CIN 1) in 3.3%. The rate of CIN 1 in HPV(+) women was higher: 13.3% vs 1.0% in HPV(-) (2=43.197; p0.001). CIN 2 and CIN 3 were reported in HPV(+) patients only. HSIL+ was diagnosed in 7.9% of HPV(+) females (2=39.778; p0.001). Conclusion. Thus, the study results showed that the mean infection rate of HCR HPV in women of the Kemerovo region at the age of 2165 years is 17.8% and decreases with age. HPV subtype 16 is predominant; subtypes 31, 35, and 33 were less common. In HPV-positive women, abnormal findings of cytological examination were significantly more common.